2022
DOI: 10.1007/s00586-022-07308-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal odontoidectomy: a long-term follow-up results for a cohort of 21 patients

Abstract: Background Endoscopic endonasal odontoidectomy (EEO) has been described as a potential approach for craniovertebral junction (CVJ) disease which could cause anterior bulbomedullary compression and encroaching. Due to the atlantoaxial junction’s uniqueness and complex biomechanics, treating CVJ pathologies uncovers the challenge of preventing C1–C2 instability. A large series of patients treated with endonasal odontoidectomy is reported, analyzing the feasibility and necessity of whether or not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The procedure was performed by using total intravenous anesthesia to allow intraoperative neuromonitoring (IONM). Once reached the lower clivus and the CVJ by using expanded endoscopic endonasal approach—as already reported in previous papers by the senior author ( 16 19 )—a huge mass was encountered into the rhinopharynx, and there was no chance to harvest the usually reverse U -shape flap. Therefore, a right naso-septal flap (NSF) was harvested with a laser.…”
Section: Case Descriptionmentioning
confidence: 58%
“…The procedure was performed by using total intravenous anesthesia to allow intraoperative neuromonitoring (IONM). Once reached the lower clivus and the CVJ by using expanded endoscopic endonasal approach—as already reported in previous papers by the senior author ( 16 19 )—a huge mass was encountered into the rhinopharynx, and there was no chance to harvest the usually reverse U -shape flap. Therefore, a right naso-septal flap (NSF) was harvested with a laser.…”
Section: Case Descriptionmentioning
confidence: 58%
“…In the last few years, this paradigm shift has also been clearly demonstrated in the management of CVJ pathologies [ 17 , 24 , 57 , 74 ]. In 2022, Perrer et al reported on their surgical series of 21 patients who underwent endoscopic endonasal odontoidectomy with favorable clinical courses at long-term follow-up, even in those cases with C1 arch preservation without posterior fixation [ 53 ], in line with the preliminary findings by Mazzatenta et al [ 46 ].…”
Section: Novelties For Safer Cvj Surgerymentioning
confidence: 78%
“…The ongoing advancement in endoscopic skull base surgery has been transplanted to CVJ surgery to address anterior pathologies through a direct approach exploiting a close-up view of the relevant anatomy [ 16 , 21 , 53 , 69 ]. In the past, microscopic transoral approaches proved to be effective treatments of oncologic, traumatic, and degenerative diseases of the CVJ.…”
Section: Novelties For Safer Cvj Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Another frequently reported complication in adults was pneumonia, which may be related to aspiration. 4,9,[16][17][18][19][20] In the pediatric population, there were several cases of reintubation due to aspiration. 12,21 There was one case of prolonged postoperative intubation for 3 days in an 11-year-old male with Down syndrome.…”
Section: Discussionmentioning
confidence: 99%